A new species and new records of the genus Neotarsonemoides Kaliszewski, 1984 (Acari: Tarsonemidae) from East Azerbaijan province, Northwestern Iran - Gheblealivand, Saeide S.; Irani-Nejad, Karim Haddad; Manzari, Shahab; Vahed, Mohammad Moghadam; Magowski, Wojciech Ł. (Zootaxa, 2016)
Mites of the genus Neotarsonemoides Kaliszewski, 1984 (Acariformes: Tarsonemoidea: Tarsonemidae) were collected in the East Azerbaijan province, Northwestern Iran. Neotarsonemoides (N.) marandicus sp. nov. is described and illustrated. Other species collected include: Neotarsonemoides (N.) evae Magowski, 2002 , N. (N.) multiplex (Kaliszewski, 1983) and N. (N.) occultus (Kaliszewski, 1983) which represent the first records of these species outside of their type locality. Neotarsonemoides (N.) polonicus (Willmann, 1949) and N. (Ototarsonemus) alatus (Livshits, Mitrofanov and Sharonov,1979) are new records for the fauna of Asia, as well as the first record of the subgenus Ototarsonemus in Western Asia. A re-description and illustrations of N. (O.) alatus are provided. An identification key to females of the genus Neotarsonemoides in Iran is provided.